ANALISIS DAMPAK PMA NO.12 TAHUN 2016 TENTANG BIAYA NIKAH GRATIS DI KUA KECAMATAN BUNUT MENURUT HUKUM KELUARGA ISLAM - Millah Shadiqoh (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2022)
This research is motivated by the increasing number of free wedding events (Rp.0) at KUA Bunut District, which is carried out by brides with low education and economic categories. This thesis is the result of field research at KUA Bunut District, Pelalawan Regency. The study was conducted to analyze the implementation and impact of the Minister of Religion Regulation (PMA) No. 12 of 2016 concerning free marriage fees, at the KUA of Bunut District and the views of Islamic family law on these rules in the Maqashid sharia frame.This research data was collected from the Regulation of the Minister of Religion Number 12 of 2016 as primary data, as well as interviews with the parties implementing this regulation, namely 5 KUA officers in Bunut sub-district, and 10 brides who registered their marriage at KUA Bunut sub-district for free.The results of this study indicate First, in the implementation of PMA Number 12 of 2016 cannot be realized, due to the ignorance of the KUA and the bride regarding this rule, in addition to the previous rules, namely PP number 48 of 2014 and also PP number 19 of 2015, have similarities, in in terms of content so that the KUA still uses these rules, and many brides prefer to carry out marriages for free during the KUA Operational hours and its implementation in the KUA Office, Second, the impact of the Minister of Religion Regulation No. 12 of 2016 concerning Free Marriage Fees outside the KUA in the KUA Bunut District, divided into 2 parts, namely positive and negative impacts for both the bride and the KUA in Bunut sub-district. Third, while in the view of Islamic family law in the Maqashid Sharia concept, this rule is considered to be able to bring harm compared to Mashlahat, this is not in accordance with the goal of Maqashid Sharia, namely maintaining offspring. (hifzdu Nasab).That way, this rule cannot be implemented properly and it is feared that it will cause problems in the future for the bridal couple in fostering the Sakinah mawaddah warrahmah family, which is the dream of the bride and groomKeywords : Marriage, Religion, Minister, Goal